Smart Retail in Market Place using IoT Technology - Mohd Sokri, Abdul Rahman; Aizan Ubin, (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, smart retail systems using IoT technology are mostly applied in the sales industry worldwide. The smart retail system can increase product sales and usage, which will surely help more in data collection or sales reports because the output obtained from this system is more accurate and systematic. This case study is for developing smart retail in the marketplace using IoT technology. In retail, some of the mistakes made by sellers are that they are not alert to the quantity or stock left on their sales shelf, or maybe products are missing from the shelf. This project aims to develop a smart retail system to monitor and collect data on the number of products and customer presence. Therefore, a new concept was developed with a smart shelf system. Hibiscus Sense ESP32 is used as a microcontroller that controls all system processes. Ultrasonic sensors and IR sensors are used to detect the quantity of stock on the shelf, while an LCD is used to display the price. The output displays in the data stream are “Has/No Presence” for the IR Sensor and “Quantity” for the ultrasonic sensor through the Favoriot platform. When the system determines that the quantity of stock at the sales shelf is less than three, an alert notification from Favoriot is sent through email. Based on this smart retail using IoT technology, the smart shelf can be used as an alternative to a small marketplace.